Proactive regional policy: What a new policy to avoid socio-economic disruptions could look like - Jens Suedekum (Forum for a New Economy, 2022)
Proactive regional policies to aide local transformation processes are in the limelight these days. This paper firstly discusses the big paradigm shift in mainstream economics towards this newly gained prominence of place-based policies. Afterwards, the paper introduces the most voluminous case in Germany, the coal exit. My analysis suggests that the three involved lignite mining areas, which have received unusual amounts for structural support, must realize that they are role models. But a preliminary assessment suggests that the resources will mostly flow into rather conventional spending categories. There is little evidence for moonshot projects or innovative novel paths that only those regions could try out – given the unique circumstances they are in. This misses the chance to experiment how proactive regional policies could exploit their full potential.
Keywords: L5; L52; L62; L71; 330; proactive regional policy; automobile industry; coal- /lignite-exit; innovative policies